ANALISIS ANALISIS MAKNA DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER:KAJIAN SEMANTIK - Timbu Dona, Supriati Maya; Koroh, Lanny Isabela Dwisyahri (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This study analyze lexical, contextual and symbolic meanings in the novel Bumi Manusia by Pramoedya Ananta Toer using a semantic approach. The research employs a descriptive qualitative method, focusing on excerpts from the novel that contain dominant and relevant meanings for the study. The analysis reveals that Pramoedya consistently utilizes the power of language to convey social criticism, human values and reflections on identity and struggle through these three layers of meaning. Lexical meaning are evident in the use of words that directly express injustice, racism and gender subordination. Contextual meanings appear in phrases and sentences shaped by the social and psychological situations of the character, while symbolic meanings emerge through symbols that reinforce the ideological and moral messages in the text. These findings demonstrate the complexity of meaning in Bumi Manusia and expand the scope of semantic studies in Indonesian literature, particularly in understanding social and cultural dynamics during the colonial period.